2022
DOI: 10.1097/spv.0000000000001228
|View full text |Cite
|
Sign up to set email alerts
|

Centering Group Treatment for Women With Interstitial Cystitis/Bladder Pain Syndrome: A Qualitative Analysis

Abstract: ImportanceWomen with interstitial cystitis/bladder pain syndrome (ICBPS) face challenging treatment and feelings of isolation. Centering models of group medical visits have been successful in other spheres but have not been explored in ICBPS therapy.ObjectiveWe sought to describe opinions of women with ICBPS regarding Centering visits, including advantages, experience, and barriers to participation and efficacy.Study DesignPatients who attended Centering visits participated in a focus group and/or filled out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…It is also possible, as noted in our qualitative work, that a great deal of learning about management strategies and self-efficacy takes place in Centering, that patients in Centering pick up more tools to self-manage their ICBPS than other patients. 41 A randomized controlled trial found mindfulness-based stress reduction to be beneficial adjuvant therapy for patients undergoing treatment for ICBPS, further supporting the findings of the current study. 14 This is one of the first studies in ICBPS we are aware of that diligently measures monthly symptoms for up to 12 months.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It is also possible, as noted in our qualitative work, that a great deal of learning about management strategies and self-efficacy takes place in Centering, that patients in Centering pick up more tools to self-manage their ICBPS than other patients. 41 A randomized controlled trial found mindfulness-based stress reduction to be beneficial adjuvant therapy for patients undergoing treatment for ICBPS, further supporting the findings of the current study. 14 This is one of the first studies in ICBPS we are aware of that diligently measures monthly symptoms for up to 12 months.…”
Section: Discussionsupporting
confidence: 85%
“…This could explain the initial benefits reflected in pain scores among women engaging in Centering therapy because Centering mediated care beyond medical therapy alone by introducing patients to various modes of alternative treatment. It is also possible, as noted in our qualitative work, that a great deal of learning about management strategies and self-efficacy takes place in Centering, that patients in Centering pick up more tools to self-manage their ICBPS than other patients 41 . A randomized controlled trial found mindfulness-based stress reduction to be beneficial adjuvant therapy for patients undergoing treatment for ICBPS, further supporting the findings of the current study 14 …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations